2019
DOI: 10.1111/jog.13883
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Comparison between 200, 400 and 600 microgram rectal misoprostol before cesarian section: A randomized clinical trial

Abstract: Aim: Compare the effectiveness of administration of different doses of rectal misoprostol before cesarean section to reduce intra-and postoperative blood loss. Methods: A double-blind randomized clinical trial including 453 term pregnant woman scheduled for elective cesarean section where participants received either 200-, 400-or 600-μg misoprostol rectally before cesarean section. Study medications were administered after catheter insertion and shortly before skin incision. Primary outcome measures were intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In our study in terms of hemoglobin and hematocrit values demonstrated the postoperative values were statistically higher in the misoprostol group than in the non-misoprostol group (only oxytocin infused group). In several publications in the literature similar to the present study, it has been emphasized that the preoperative and postoperative administration of rectal misoprostol reduces postpartum blood loss 13,24,25,26 . In their meta-analysis of 17 studies including 3174 women having undergone cesarean section, Conde-Agudelo et al emphasized that the postoperative administration of misoprostol and oxytocin in combination significantly reduced postpartum hemorrhage compared to the postoperative administration of oxytocin alone 27 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In our study in terms of hemoglobin and hematocrit values demonstrated the postoperative values were statistically higher in the misoprostol group than in the non-misoprostol group (only oxytocin infused group). In several publications in the literature similar to the present study, it has been emphasized that the preoperative and postoperative administration of rectal misoprostol reduces postpartum blood loss 13,24,25,26 . In their meta-analysis of 17 studies including 3174 women having undergone cesarean section, Conde-Agudelo et al emphasized that the postoperative administration of misoprostol and oxytocin in combination significantly reduced postpartum hemorrhage compared to the postoperative administration of oxytocin alone 27 .…”
Section: Discussionsupporting
confidence: 72%
“…Fever due to misoprostol is caused by a centrally mediated effect of brain 28 . In their study involving 453 pregnant women, Sweed et al found that the incidence of fever and shivering was higher in the patients who were administered high dose rectal misoprostol (≥800 mg) 26 . In the present study, while the shivering rate was 7.5% in the misoprostol group, it was 1.7% in the non-misoprostol group.…”
Section: Discussionmentioning
confidence: 99%
“…Many such other studies have been done which develop conspiracy in the use of transrectal misoprostol or intravenous oxytocin in actively managing the stage three of labour. To bring a conclusion to these controversies this study will help study and compare the effectiveness of 600mcg misoprostol with 10IU oxytocin given transrectally or intravenous respectively in managing the third stage of labour actively [10]. Studies related to labour and postpartum hemorrhage was reviewed [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Shivering and increased body temperature is also seen with the misoprostol usage in third stage of labour [9]. Slower rate of absorption and lower peak levels is seen with rectal route of administration in comparison to sublingual and oral routes, however incidence of adverse effects is reduced with rectal route [10].the initial onset of action is fast and initial uterotonic effect is also strong with oral solution and sublingual routes. High incidence of shivering and rise in temperature is seen with these routes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation